BEHAVIORAL AND COGNITIVE CORRELATES OF WEIGHT LOSS IN A WORKSITE WEIGHT LOSS INTERVENTION. - Batra, Payal. (2017)
Abstract: Overweight and obesity remain at epidemic levels and are associated with increased morbidity and mortality as well as increased health care costs. Both behavioral and lifestyle interventions are recommended for weight loss in obese individuals, but the widely-suggested goal of 5-10% weight loss to achieve significant health benefits is not routinely achieved even in intensive weight loss intervention studies. Identifying behavioral and cognitive correlates associated with successful weight loss in different types of interventions could inform the development of more effective and sustainable programs for weight control. Worksites are increasingly being suggested as important settings for body weight management interventions. However, to date, there have been no studies examining predictors of weight loss in worksite weight control interventions. We examined changes in behavioral and cognitive measures in a group-randomized controlled trial of a behavioral weight loss intervention versus wait-listed control at worksites. Analysis presented here compare participants at the intervention sites versus those at the control sites. Questionnaires administered at baseline and at 6 months measured eating behaviors (Eating Inventory), food cravings (Craving Inventory, Food Cravings Questionnaire-State and Trait), weight self efficacy (Weight Efficacy Lifestyle Questionnaire) and quality of life (WHO-BREF quality of life questionnaire). These indices, as well as measures of program adherence such as frequency of self-monitoring of body weight and meeting attendance were examined as correlates of weight change. To better inform future efforts in worksites we developed an intervention specific feedback questionnaire to determine which programmatic components of the intervention were most useful to participants. Weight change was greater in the intervention participants (I) than in participants in the wait-listed control (C), (Mean ±SD ∆ I=-8.1 kg ± 6.8 kg, ∆ C=+0.9 kg ± 3.6 kg, p<0.001). The intervention resulted in increased restraint (∆I=5.43±4.25, ∆C=0.29±3.80, p<0.001), decreased disinhibition (∆I=-2.50±3.63, ∆C=0.66±1.85, p<0.001) and decreased hunger (∆I=-2.79±3.13, ∆C=0.56±2.63, p<0.001) relative to the control group. These individuals also showed significant reductions in all aspects of craving, increases in weight self efficacy and its 5 situational dimensions, and improvements in the 4 quality of life domains. Within the intervention group, weight change was significantly correlated with decreased hunger (r=0.36, p=0.001), decreased food craving-trait (r=-0.24, p=0.04), increased total weight self efficacy (r=-0.34, p=0.01), session attendance (r=-0.4, p=0.003) and frequency of weight self monitoring (r=-0.3, p=0.029). All programmatic components were perceived as useful by participants and each component was correlated with weight change. These findings demonstrate that positive changes in behavioral and cognitive attributes can be achieved in the context of a multi-component group based weight loss program implemented within a worksite setting and advance the understanding of behavioral and cognitive attributes as determinants of weight loss. These findings also provide guidance for refinement of future worksite weight loss interventions.; Thesis (Ph.D.)--Tufts University, 2012.; Submitted to the Dept. of Biochemical and Molecular Nutrition.; Advisor: Sai Das.; Committee: Susan Roberts, Tammy Scott, Edward Saltzman, and Gerard Dallal.; Keywords: Nutrition, and Behavioral psychology.